Mechanism of stress heart damage in the animals of different sensitivity to hypoxia - O. V. Denefil; Iu. M. Ordynskyi (Kazimierz Wielki University, 2020)
Hypoxia and resistance to it is the main in today data sitiuayion in the world. The aim of the study was to determine level of myocardium damage and corresponding of it with cytokines level in high- and low-resistance to hypoxic hypoxia rats (HR, LR) in different models of immobilization stress. Material and methods of investigation. The experiments were performed on 144 outbred HR and LR aged 5.5-6 months, dividing into 3 groups - control and 2 with different model of immobilizing stress. It was determined morphological changes of myocardium and concentration of interleukins 1beta, 2, 4, 6, 10 (IL-1beta, IL-2, IL-4, IL-6, IL-10), tumor necrosis factor alpha (TNF-alpha) in the blood serum. Results. The morphological investigation showed the bigger damage effect in LR animal, than in HR rats. Damage effects were higher in males, than in females. The stress repeating every 72 hours (stress 2) had higher damage in myocardium, than stress repeating every 24 hours (stress 1). We corresponds the results with cytokines level. High congenital resistance to hypoxia is associated with an increased content of anti-inflammatory cytokines (in males IL-4, in females IL-10). Intact males, compared with females, have a higher production of pro-inflammatory cytokines (IL-6, TNF-alpha). At stress1 inHR males, compared with HR females, were lower contents of IL-10, higher level of IL-1beta, IL-4, IL-6, TNF-alpha. At stress1 inLR males, compared with LR females, were lower contends of IL-10, IL-2. The morphological changes were more in males, that's why higher level of anti-inflammatory cytokines IL-10 really has protection in HR and LR females' animals. At stress2 inHR male, compared with HR female, were lower contents of IL-1beta and IL-10, higher IL-2 and IL-6. At stress2 inLR males, compared with LR females, were higher level of IL-10, IL-6, lower contents of IL-2, IL-4. The morphological changes were more in males, that's why pro-inflammatory cytokines IL-6 really take place in damage of myocardium in males with different resistance animals. Conclusion. High congenital resistance to hypoxia is associated with smaller destroying of the myocardium layer in immobilizing stress, which correspond with increased content of anti-inflammatory cytokines IL-4 and, IL-10. Higher damage of myocardium in immobilizing stress correspond with higher production of pro-inflammatory cytokines (IL-6, TNF-alpha).